Data Privacy Compliant Validation of Health Insurance Claims Data: the IDOMENEO Approach - Behrendt, Christian-Alexander; Schwaneberg, Thea; Hischke, Sandra; Müller, Tobias; Petersen, Tom; Marschall, Ursula; Debus, Sebastian; Kriston, Levente (Das Gesundheitswesen, 2020)
Recently, health insurance claims have regained the attention of the scientific community as a source of real-world evidence in health care research and quality improvement. To date, very few studies are available which investigate the validity of health insurance claims; these may be affected by bias from several sources, such as possible upcoding of co-morbidities and complications for reimbursement advantages. The IDOMENEO study investigates the inpatient treatment of peripheral arterial disease (PAD) comprehensively using various data sources with a consortium involving experts from health care research and data privacy, a large health insurance fund, biostatisticians, jurists, and computer scientists. Prospective registry data were collected from 30–40 vascular centres in Germany using the GermanVasc registry. In addition, health insurance claims data were prospectively collected from BARMER, the second largest health insurance fund in Germany. The consortium is currently developing a data privacy compliant method of health insurance claims data validation, the methodological foundations of which are described here.
Keywords: Periphere arterielle Verschlusskrankheit; Krankenkassendaten; Register; Routinedaten; Qualitätsentwicklung; Datenvalidität